IMPLEMENTATION OF THE TNI MANUNGGAL TO BUILD VILLAGES (TMMD) PROGRAM IN PAREPARE CITY - Ramadhani, Delia; Sakawati, Herlina; Nur, Andi Cudai (Universitas Negeri Makassar, 2025)
This study aims to find out the Implementation of the TNI Manunggal Village Building Program (TMMD) in Parepare City. This type of research is qualitative with data collection techniques carried out by observation, interviews, and documentation. The data analysis techniques used consist of data reduction, data presentation and conclusion drawn. The results of the research show that the TNI Manunggal Pembangunan Desa (TMMD) Program in Parepare City from the results of interviews shows that the implementation of the TNI Manunggal Pembangunan Desa (TMMD) program by involving the local government in Parepare City helps the community to be empowered, thereby improving the welfare of the community through physical and non-physical development. In this study, Edwards III theory is used by considering four factors in the implementation of public policy, namely Communication, Resources, Disposition, and Bureaucratic Structure. There are indicators that are not good, namely Resources, so it is considered an inhibiting factor in the implementation of the TNI Manunggal Pembangunan Desa (TMMD) program. Meanwhile, other indicators such as Communication, Disposition, and Bureaucratic Structure are considered to be quite good. The need to increase resources in the TNI Manunggal Pembangunan Desa (TMMD) program budget to continue the program